Diversity of clustered protocadherin-α genes in neuronal identity and its role in short-term specific associative memory formation - Tomoki Osuka; Hiroki Yamamoto; Takeshi Yagi (Scientific Reports)
Abstract Clustered protocadherins (cPcdh) are cell adhesion molecules with 58 isoforms, essential for neural circuit formation and higher cognitive functions. This study investigated the impact of reduced cPcdh-α diversity on cognitive function using mutant mice. Behavioral tests revealed that cPcdh-α1-12 mice exhibited specific memory impairments ranging from a few seconds to 2 h short-term memory, while memory from 24 h to 2 weeks long-term memory remained intact. Notably, no abnormalities in appearance or spontaneous behavior were observed in cPcdh-α1-12 mice, suggesting that the deficits were specific to short-term memory. Furthermore, a comprehensive analysis of neural activity during memory recall in 2 h short-term memory and 24 h long-term memory following showed significant reductions in the hippocampus, amygdala, and retrosplenial cortex during short-term memory tasks. No such reductions were observed during long-term memory recall. These results suggest that short-term and long-term memory are supported by partially distinct neural circuits and underscore the critical role of cPcdh-α diversity in establishing the neural pathways necessary for short-term memory retrieval.